Sport nutrition for coaches - Bonci, Leslie (Human Kinetics, 2009)
Sport Nutrition for Coaches answers the call from coaches and other fitness professionals for a text to help them teach athletes the nutrition habits for optimal performance. This practical book, written specifically for coaches by sport nutrition expert Leslie Bonci, includes several planning tools